F(X)=6X^2+2X-12

F(0)

F(2)

F(-2)

F( SQUAREROOT 2)

F(X+1)

F(-X)

please note that:

1) setting x0 0, we get f(0) = -12;

2) setting x =2, we get f(2) = 6*4+4-12 = 16;

3) setting x= -2, we get f(-2) = 6*4 -4 -12 = 12;

4) setting x= sqrt(2), we get f( sqrt(2)) = 6*2+ 2*sqrt(2) -12 = 2*sqrt(2);

5) setting x--->x+1, we get f(x+1) = 6 (x+1)^2 +2(x+1) -12 =

= 6x^2 + 6 +12 x +2x + 2 -12 = 6x^2 - 2x -12;

setting x---> -x we get: f(-x) = 6x^2 - 2x -12

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up